Metformin as a Potential Geroprotective Agent: Mechanisms, Clinical Evidence and Implications for Healthy Aging - Kawalec, Paulina; Bronikowski, Kamil; Ryszkowski , Maksymilian; Fornal, Krystian; Będkowska-Kuśmierek, Natalia; Zaborowska, Sabina; Pawlak , Paulina; Wojcieszuk , Olaf; Starczewski, Łukasz; Babik, Adrianna (Journal of Education, Health and Sport, 2026)
Background: Population aging represents a major medical and socioeconomic challenge worldwide. The increasing prevalence of age-related diseases, including cardiovascular disorders, neurodegeneration, cancer, and metabolic dysfunction, highlights the need for strategies aimed at extending healthspan rather than lifespan alone. In this context, pharmacological agents that modulate fundamental biological processes of aging have attracted significant attention. Metformin has emerged as a potential candidate beyond its established role in the treatment of type 2 diabetes mellitus. Aim: This narrative review aimed to evaluate current evidence regarding the potential geroprotective properties of metformin, with particular emphasis on underlying molecular mechanisms and available clinical data. Materials and Methods: A narrative literature review was conducted using the PubMed database. Articles published between January 2015 and March 2025 were identified using the keywords “metformin”, “aging”, “longevity”, and “geroprotection”. Peer-reviewed original studies and review articles in English were included, while case reports and non-peer-reviewed publications were excluded. Results: Evidence indicates that metformin influences multiple pathways involved in aging, including activation of AMP-activated protein kinase (AMPK), inhibition of the mechanistic target of rapamycin (mTOR), modulation of mitochondrial metabolism, reduction of oxidative stress, and attenuation of chronic inflammation. Observational studies suggest associations with reduced incidence of age-related diseases and improved survival; however, direct evidence in non-diabetic populations remains limited. Conclusions: Metformin demonstrates properties consistent with potential geroprotective effects. However, well-designed randomized controlled trials are required to confirm its efficacy and safety in the context of healthy aging.